1998
DOI: 10.1074/jbc.273.44.28878
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Bound to CD44 on Keratinocytes Is Displaced by Hyaluronan Decasaccharides and Not Hexasaccharides

Abstract: Abundant hyaluronan is present between epidermal keratinocytes. However, virtually nothing is known regarding its organization in the limited extracellular space between these cells. We have used metabolic labeling with [ 3 H]glucosamine and [ 35 S]sulfate and a hyaluronan-specific biotinylated probe to study the metabolism of hyaluronan and its localization in monolayer cultures of a rat epidermal keratinocyte cell line. Hyaluronan (ϳ20 fg/cell) was present on the apical and lateral surfaces of the cells in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
94
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 61 publications
8
94
0
Order By: Relevance
“…The same finding was observed when GFP-xlHas1 was transfected into oocytes (14). REKs are also known to display cell surface hyaluronan as patches, 100 -200/ cell, perhaps corresponding to the HAS sites (35). The present data, a part of which was obtained from high resolution threedimensional reconstructions of live cells, provided important novel information on this issue, suggesting that these GFP-HAS enrichment sites were actually cell surface protrusions.…”
Section: C-terminal Truncation Of Has3 and Exit From Er-supporting
confidence: 84%
“…The same finding was observed when GFP-xlHas1 was transfected into oocytes (14). REKs are also known to display cell surface hyaluronan as patches, 100 -200/ cell, perhaps corresponding to the HAS sites (35). The present data, a part of which was obtained from high resolution threedimensional reconstructions of live cells, provided important novel information on this issue, suggesting that these GFP-HAS enrichment sites were actually cell surface protrusions.…”
Section: C-terminal Truncation Of Has3 and Exit From Er-supporting
confidence: 84%
“…Specifically, perinuclear CD44 staining of sHA-treated endothelial cells was not different from that of untreated cells (36), indicating that the sHA uptake and specific NF-B-dependent signaling was not mediated by CD44. The notion that sHA fragments interact with cells independent of CD44 is supported by recent findings from Culty et al (31) and Tammi et al (42). On the basis of HMW-HA competition studies, these investigators concluded that only sHA fragments of at least 6-to 10-oligosaccharide length, but not smaller fragments, bind to CD44 on endothelial cells or keratinocytes, respectively.…”
Section: Discussionmentioning
confidence: 84%
“…Hyaluronan digestion was carried out using 50 g/ml of bovine testicular hyaluronidase (BTH) for 3 h at 37°C. Equal volumes of both undigested and BTH-digested products derived from two cell lines were loaded onto a 5-20% gradient gel (19), along with BTH-digested and undigested pure polymeric HA from human umbilical cord acting as positive controls. The gel was then stained with 1% Alcian blue in 3% acetic acid, destained, and subsequently stained with silver nitrate (19).…”
Section: Methodsmentioning
confidence: 99%